Emilia’s voice: Shakespeare's take on feminism in Othello - Rodrigues, Karen Danielle Lima (Revista Fronteira Digital, 2023)
Shakespeare’s female representation and the way his female roles are portrayed and interpreted have ignited the curiosity and admiration of many scholars. The article, therefore, intends to discourse on the important role Emilia holds in the play Othello. How does her secondary role bring such significance to the play? What voice does she have? Who is, in fact, Emilia? Although many centuries have passed since the publication and original enactment of this play, Emilia’s role brings forth many interesting debates that are pertinent to our present society.